2016
DOI: 10.1021/acs.est.6b00161
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Reactivity Associated With Electronic Monitoring of Environmental Health Interventions—A Cluster Randomized Trial with Water Filters and Cookstoves

Abstract: Subject reactivity--when research participants change their behavior in response to being observed--has been documented showing the effect of human observers. Electronics sensors are increasingly used to monitor environmental health interventions, but the effect of sensors on behavior has not been assessed. We conducted a cluster randomized controlled trial in Rwanda among 170 households (70 blinded to the presence of the sensor, 100 open) testing whether awareness of an electronic monitor would result in a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…However, longer-term SUMs data revealed an increase in cooking on traditional stoves in urban households and an associated decrease in HM-5000 usage following the end of the KPT monitoring period. households is likely to be slightly higher than what was measured during the KPT 15 . Participants in control groups were presumably less likely to overestimate their stove use as a result of the pressure felt to satisfy study evaluators.…”
Section: Adoption Of the Hm-5000 In Householdsmentioning
confidence: 60%
See 1 more Smart Citation
“…However, longer-term SUMs data revealed an increase in cooking on traditional stoves in urban households and an associated decrease in HM-5000 usage following the end of the KPT monitoring period. households is likely to be slightly higher than what was measured during the KPT 15 . Participants in control groups were presumably less likely to overestimate their stove use as a result of the pressure felt to satisfy study evaluators.…”
Section: Adoption Of the Hm-5000 In Householdsmentioning
confidence: 60%
“…Although the HM‐5000 remained the primary stove in the urban user group after the KPT monitoring period, this notable decline in usage is likely an example of the Hawthorne effect, which describes a reaction by individuals to change their behavior in response to their being observed. Based on the usage monitoring that followed the end of the KPT, traditional stove usage by HM‐5000‐owning households is likely to be slightly higher than what was measured during the KPT. Participants in control groups were presumably less likely to overestimate their stove use as a result of the pressure felt to satisfy study evaluators.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Jagger and Jumbe (2016) found that willingness to adopt ICS in Malawi was lower among households with a large labor force for fuel collection [70]. However, other studies find that larger families are more likely to adopt ICS [31,37,71]. In this regard, Onyeneke et al (2017) state that cooking for a large family group usually requires more time and fuelwood, so large households tend to adopt more efficient cooking technologies than small households [31].…”
Section: Socio-demographicsmentioning
confidence: 99%
“…[7][8][9][10][11][12] For example, surveys are subject to bias due to recall error and the Hawthorne effect. 12 Direct sensor-based stove-use monitoring may provide an alternative, less biased approach. These studies employ stove-use monitors (SUMs) that measure temperature as a proxy for stove usage.…”
Section: Introductionmentioning
confidence: 99%